(untitled) (Research, Society and Development, 2019)
The work category has undergone profound transformations since the last decades of the twentieth century, especially since 1995 under the government of Fernando Henrique Cardoso. In this, capital has been restructured from neoliberalist politics, which saw in the work the opportunity to broaden its eagerness for more profit; now, far beyond gaining profits on the strength of the proletariat, the quest is for new conditions to make the worker even more submissive. The labor reform, Law No. 13467, made official in 2017, brought the possibility of collective agreements; supposedly, a form of negotiation between employer and employee. The aim of the research is to reveal the worker’s situation in the face of such changes and to outline the risks hidden in the new labor laws. This research is a case study with a bibliographical, methodological and qualitative approach. Based on a bibliographical research, the work sought to base its theme through the thought of renowned authors, as well as in laws so that one can have the clarity of what this labor reform is and its possible consequences. It was concluded that labor agreements are a great trap, where the worker is forced to make changes in his life, so that he is not outside the labor market and although the injury to the worker occurs, among other things, the instability in your service station.